The Representation of Foreign and Indonesian Cultures in English Text Books for Junior High School in Indonesia - Jismulatif Jismulatif; Dahnilsyah Dahnilsyah; Syofia Delfi; Indah Tri Purwanti (STAI Hubbulwathan Duri, 2022)
The aim of this study is to examine the representation of foreign and Indonesian cultural content in three English textbooks of 9th-grade junior high school students in Indonesia. This is descriptive qualitative research and uses a multicultural perspective approach. The data was taken from three English texts books, Think Globally Act Locally, English in Focus and Bright An English. The content analysis of this textbook was carried out using four aspects of the cultural dimension; product, practice, perspective, and person. The data was analyzed, from two perspectives; the perspective of cultural components and the perspective of cultural presentation levels. Based on the data analysis, it has been discovered that Indonesian culture is overrepresented in the three English textbooks, resulting in a poor presentation of foreign cultural elements. Product dimension is the most prevalent in textbooks, followed by person dimension, practice dimension, and perspective dimension based on percentage distribution. The cultural content of the English textbooks reveals an unbalance between foreign and Indonesian cultures. Most of the English-language textbooks contain Indonesian cultures, while only a few include other cultures. In comparison to Indonesian cultures, there are fewer foreign cultural representations in the English textbooks. It is recommended that English textbooks should include more materials from the cultures of English-speaking countries.